Evaluation and Physical Stability Effervescent Powder of Okra Leaves Extract (Abelmoschus esculentus) as an Antidiabetic Supplement - Aditama, Agnis Pondineka Ria; Ramadhani, Alfi Nur; Falahi, Asa; Rashati, Dewi (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 3 (2023): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v3i0.2466, 2023)
Diabetes Mellitus (DM) is a disease characterized by hyperglycemia, and the most frequently encountered is type 2, which requires oral anti-diabetic therapy. Economic and socio-cultural factors also influence people in choosing alternative medicine. Okra ( Abelmoschus esculentus (L.) Moench) is a medicinal plant containing the active substances flavonoids, α-cellulose, and hemicellulose in its leaves which have anti-diabetic properties, especially type 2 DM. This research aims to make a formula and determine the physical stability of the anti-diabetic supplement preparations in the form of effervescent powder from okra leaves extract. The method used is to make okra leaves extract effervescent powder in 3 formulations with a combination percentage of acid (tartaric and citric acid) and base (sodium bicarbonate) F1 = 27.87%: 26.8%, F2 = 26.05%: 28, 62%, F3 = 24.22%: 30.45%. The preparation evaluation includes organoleptic tests, flow rate, water content, effervescence time, pH, and hedonics for 1 and 14 days of storage at cool temperatures (8-15°C), room temperature (15-30°C), and warm temperature (30-40°C). The results showed that variations in acid-base concentration affected organoleptic, physical properties (taste), flow rate, water content, effervescence time, and pH. F3 shows the best formula and is the formula that respondents like most based on texture, color, flavor, and taste parameters. A cool temperature (8-15°C) shows the best stability because of its physical stability.